Brand Engagement Strategy on Social Media in Shaping Consumer Behavior - Ian Zulfikar (Journal of Economics and Business (JECOMBI), 2025)
This study aims to analyze brand engagement strategies on social media and their influence on shaping consumer behavior. In the digital era, social media has become a primary communication channel for companies to build interactive relationships with their consumers. This study used a qualitative approach with descriptive methods. The results show that brand engagement strategies on social media, such as interactive content, storytelling, collaboration with influencers, live streaming, and loyalty programs, can increase consumer engagement and shape positive attitudes toward the brand. Consumers who actively engage with brand content demonstrate higher levels of loyalty and interest, and are more likely to respond positively to the product. However, the effectiveness of this strategy is influenced by the company's ability to build trust, maintain data transparency, manage budgets, address negative content, and adapt to constantly changing social media trends and algorithms.